(untitled) (CAHIERS MAGELLANES-NS, 2024)
Literary translation is a dynamic and essential process that facilitates cultural exchange, expands global literary perspectives, and preserves the diversity of world literature. This abstract explores the multifaceted role of literary translation, addressing its challenges, ethical considerations, and profound impact on literature and cultural understanding. The practice of literary translation involves intricate challenges, foremost among them being the balance between fidelity to the original text and readability in the target language. Translators must navigate linguistic nuances, cultural references, and stylistic differences to convey the author's intent faithfully while ensuring the translated work resonates with its new audience. These challenges require creativity and sensitivity to capture the nuances of language and cultural context, thereby preserving the essence of the original work. Ethical considerations play a pivotal role in literary translation, influencing decisions regarding accuracy, cultural representation, and the translator's role in interpreting the text. Maintaining authenticity and respect for the source culture is paramount, as translations have the power to shape perceptions and understanding of diverse cultures worldwide. Transparency about the translator's choices and interpretations fosters trust and enhances the reader's appreciation of the translated work's cultural richness. Beyond linguistic and cultural complexities, literary translation serves as a bridge that connects readers across borders. By making literature accessible in different languages, translators facilitate global dialogue, promote cross-cultural understanding, and nurture empathy for diverse perspectives. This exchange of ideas and narratives enriches the global literary landscape, encouraging the exploration of new genres, themes, and narrative techniques across cultures. Furthermore, literary translation contributes to the preservation and dissemination of literary heritage. Translators play a vital role in ensuring that significant works of literature, ranging from ancient epics to contemporary novels, are accessible to future generations.